(untitled) (World Bulletin of Public Health, 2024)
Nephroblastoma (Wilms tumor) is one of the most common malignant neoplasms in children. The tumor is named after the German surgeon Max Wilms, who described it in 1899. The tumor invades the kidney parenchyma and develops from degenerated (embryonic, epithelial and stromal) cells in varying proportions, destroying the affected kidney. The lymph nodes located in the region of the renal portal, para-aortic and hepatic portal are most often affected.1 By hematogenous route, they mainly metastasize to the lungs, less often to the liver.